Research and development of semi-automatic pineapple peeling and coring machine - Đặng Minh Phụng; Phạm Văn Cảnh; Trần Văn Trí (Journal of Technical Education Science, 2014)
Nowadays, pineapple products are widely used in the households. In addition to domestic market, pineapple products have been now exported to foreign countries such as the U.S.A, EU, Japan, etc ... However, the production of pineapple products is mostly manual. This decreases the productivity and competitiveness of pineapple exports. Meanwhile, in Vietnam, studies on developing pineapple peeling and coring machines, especially those related to pineapple peeling and coring machines controlled by pneumatic cylinders have not gained much interest. This paper presents the results of the research into semi-automatic pineapple peeling and coring machine with a view to mechanizing the work of pineapple peeling and coring, enhancing productivity, as well as meeting the increasing demand of the pineapple product manufacturing companies. Test results show that the semi-automatic pineapple peeling and coring machine worked well with finely – cut pineapple pieces, satisfying both food safety and aesthetic requirements. Depending on the customer demand, the products will be shaped according to the shape of cutter system.